Perkembangan dan Pengorganisasian Program Pemberdayaan Masyarakat oleh Yayasan Nurani Dunia di Purwakarta - Kurniawati, Kamilah Dwi; Rahmawati, Ismi Arsilah (UI Scholars Hub, 2025)
Non-Governmental Organizations (NGOs) play a critical role in advancing societal welfare. However, while their numbers have increased, public trust remains low, as NGOs are often perceived to lack the capacity to design and evaluate programs effectively and fail to engage local stakeholders (Bodja, 2006). Previous research has predominantly focused on NGOs' roles in enhancing community participation and social networks, overlooking the importance of program management and stakeholder relations. This article examines the development of program frameworks, program organization, and the involvement of local organizations in Yayasan Nurani Dunia, an NGO that focuses on community development and dedicated to program innovation. Using a qualitative approach, this study employs in-depth interviews and direct field observations. The findings reveal that the program framework has evolved from charity-based initiatives to sustainable empowerment programs. Additionally, program organization demonstrates strong administrative management and incorporates adequate capacity-building elements. Lastly, the engagement of local organizations is reflected in social legitimacy and material and non-material support from relevant stakeholders. Yayasan Nurani Dunia exemplifies social transformation, emphasizing holistic societal change (Lewis & Kanji, 2009).